2012
DOI: 10.1016/j.phytochem.2011.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and gene expression changes triggered by nitrogen deprivation in the photoautotrophically grown microalgae Chlamydomonas reinhardtii and Coccomyxa sp. C-169

Abstract: Microalgae are emerging as suitable feedstocks for renewable biofuel production. Characterizing the metabolic pathways involved in the biosynthesis of energy-rich compounds, such as lipids and carbohydrates, and the environmental factors influencing their accumulation is necessary to realize the full potential of these organisms as energy resources. The model green alga Chlamydomonas reinhardtii accumulates significant amounts of triacylglycerols (TAGs) under nitrogen starvation or salt stress in medium contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

31
263
0
14

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 350 publications
(308 citation statements)
references
References 72 publications
31
263
0
14
Order By: Relevance
“…Previous studies have assessed the responses of metabolic genes and proteins under non-steady state conditions when TAG accumulates (Miller et al, 2010;Boyle et al, 2012;Msanne et al, 2012;Blaby et al, 2013;Wase et al, 2014) or identified mutants that are defective for TAG accumulation or catabolism (Li et al, 2012;Boyle et al, 2012;Tsai et al, 2014;Xie et al, 2014;Ngan et al, 2015;Kajikawa et al, 2015). The relationship between starch synthesis and TAGs has also been investigated, and it appears that fixed carbon can be shunted toward TAGs when starch synthesis is blocked (Li et al, 2010a(Li et al, , 2010bWork et al, 2010;Siaut et al, 2011;Goodenough et al, 2014).…”
Section: Insps As a Metabolic Signal For Carbon Metabolismmentioning
confidence: 99%
“…Previous studies have assessed the responses of metabolic genes and proteins under non-steady state conditions when TAG accumulates (Miller et al, 2010;Boyle et al, 2012;Msanne et al, 2012;Blaby et al, 2013;Wase et al, 2014) or identified mutants that are defective for TAG accumulation or catabolism (Li et al, 2012;Boyle et al, 2012;Tsai et al, 2014;Xie et al, 2014;Ngan et al, 2015;Kajikawa et al, 2015). The relationship between starch synthesis and TAGs has also been investigated, and it appears that fixed carbon can be shunted toward TAGs when starch synthesis is blocked (Li et al, 2010a(Li et al, , 2010bWork et al, 2010;Siaut et al, 2011;Goodenough et al, 2014).…”
Section: Insps As a Metabolic Signal For Carbon Metabolismmentioning
confidence: 99%
“…Although the molecular details of the response to nitrogen starvation have received considerable attention (7,14,44) the biochemistry and molecular biology of other TAG-inducing conditions has not been explored.…”
Section: Iron Starvation Has a Major Impact On Glycerolipid Content Imentioning
confidence: 99%
“…These and other studies point to wide-ranging changes in the structure and operation of the metabolic and other cellular networks. Several studies have considered the relationships among metabolic processes, including how carbon and energy fixation by photosynthesis affects oil accumulation during N deprivation (Miller et al, 2010;Msanne et al, 2012;Johnson and Alric, 2013). However an integrated systems analysis of both the machinery and the physiological functioning of the photosynthetic apparatus during nutrient deprivation is still lacking, and this limits our understanding of the multilevel regulation of energy and carbon fluxes.…”
mentioning
confidence: 99%
“…During N deprivation in algae, energy and carbon for de novo synthesis of TAG can come directly from photosynthesis (Msanne et al, 2012) or from external carbon substrates (Wang et al, 2009;Johnson and Alric, 2013). Photosynthetic yields decrease during N deprivation, even under phototrophic conditions where cells are entirely dependent upon photosynthesis (Philipps et al, 2012;Simionato et al, 2013).…”
mentioning
confidence: 99%